Aprendizaje Basado en Competencias en las Ciencias Básicas - Jacksson Sánchez (Perspectivas Metodológicas​)
Competency-Based Learning (CBL) is one of the objects of study that has been a trend in recent years from various perspectives and educational levels. Now, this type of learning focused on the basic sciences is of great relevance since it allows the development of skills, attitudes and knowledge that can be applied in everyday life.